Reviewing military education in SAF - Fook, Bernard Weng Loo (2016)
With the emergence of the so-called ‘strategic corporal’, the demands for military education in the SAF must surely heighten. All soldiers – across the entire organisation, need to be educated about the potential strategic impact of their smallest actions.